The effect of progressive income tax on consumer spending in Iraq for the period from 1995 to 2020 (Journal of Accounting and Financial Studies ( JAFS ), 2023)
The tax legislator resorted to making several changes to the tax rates to meet the increasing government burdens, and since the increase in taxes affects the income of the taxpayers, so the research aims to show the impact of the progressive income tax on both family and government spending during the research period from 1995 to 2020, as The research problem was an attempt to answer the following question:Do progressive taxes affect the rates of household consumption expenditure and government consumption expenditure ?In order to achieve the objective of the research, a descriptive and inductive method was chosen in presenting the theoretical foundations, while on the applied side, the analytical and quantitative approach was used to analyze the financial data obtained from the General Authority for Taxes and the Ministry of Planning.The researcher reached a set of conclusions, the most important of which are:1- The imposed income tax has a positive moral effect, as the higher the tax revenue, the higher the family consumption, and this means the ineffectiveness of the method of increasing tax prices and doubling tax brackets in order to reduce consumption, as the consumerism of the taxpayer was almost constant or affected by other factors such as wealth, high prices and imitation Others and their influence on the surrounding environment and their simulation of living standards prevailing in developed countries and the lack of inclination to save and the existence of other financial obligations of individuals.2- The low ratio of income tax revenues to the size of household spending for the period from 1995 to 2020, and this confirms the absence of an economic relationship between them, and therefore the inability of income tax to influence household consumption spending, and that spending is driven by other factors in which income tax has no role, for example: the general level of prices or expectations About income or wealth in the future, where if the expectations were optimistic, they led to increased consumption, and the opposite in the case of pessimism.